Taber's cyclopedic medical dictionary CD-ROMultimedia. - Taber, Clarence Wilbur, 1870-1968. ([Philadelphia, Pa.] : F.A. Davis Co., 1997)
Medical, nursing and health professions dictionary which includes sophisticated text searching, videos and full-color animations to illustrate clinical procedures and anatomic processes. Includes hypertext links, zoom-and-pan graphics viewer, cut-and-paste and bookmark features.
Title from disc label; additional information from guide and container.
System requirements (PC): 386/33 PC or higher with SVGA 256 color monitor; Microsoft Windows 3.1 or later; 8 MB RAM; hard disk drive with at least 3 MB free; 2X CD-ROM drive; 8 bit audio, sound card required.
System requirements (Mac): 68030 processor (PowerPC recommended) with 256 color monitor; MacOS system 7.0 or later; 8 MB RAM; hard disk drive with 3 MB free; 2X CD-ROM drive; 8 bit audio; QuickTime required for video playback.
Keywords: Medicine -- Dictionaries